HIF-1α/BNIP3-Mediated Autophagy Contributes to the Luteinization of Granulosa Cells During the Formation of Corpus Luteum - Tang, Zonghao; Zhang, Zhenghong; Lin, Qingqiang; Xu, Renfeng; Chen, Jiajie; Wang, Yuhua; Zhang, Yan; Tang, Yedong; Shi, Congjian; Liu, Yiping; Yang, Hongqin; Wang, Zhengchao (Frontiers in Cell and Developmental Biology, 2021)
During the luteinization after ovulation in mammalian ovary, the containing cells undergo an energy consuming function re-determination process to differentiate into luteal cells under avascular environment. Previous evidences have delineated the contribution of autophagy to the cell differentiation and the catabolic homeostasis in various types of mammalian cells, whereas few interest had been focused on the involvement of autophagy in the luteinization of granulosa cells during the formation of early corpus luteum. Herein, the present study investigated that expression and contribution of autophagy during granulosa cell luteinization and early luteal development through in vivo and in vitro experiments. The results clearly demonstrated that HIF-1α/BNIP3-mediated autophagy plays a vital role in the luteinization of granulosa cells during the early luteal formation in vivo and in vitro. In the neonatal corpus luteum, HIF-1α up-regulated BNIP3 expressions, which contributed to the autophagic initiation by disrupting beclin1 from Bcl-2/beclin1 complex and protected cells from apoptosis by curbing the skew of mitochondria balance under avascular niche. Notably, Inhibition of HIF-1α activity by echinomycin enhanced the levels of cytoplasmic cytochrome c and cell apoptosis in the nascent corpus luteum. These findings revealed that HIF-1α/BNIP3-mediated autophagy enabled the process of granulosa cell luteinization and protected the granulosa-lutein cells from further apoptosis under hypoxia niche. To our knowledge, the present study firstly clarified that HIF-1α/BNIP3-mediated autophagy contributes to the luteinization of granulosa cells during the formation of pregnant corpus luteum, which will help us further understanding the luteal biology and provide us new clues for the treatment of luteal insufficiency.